Pengaruh Konsep Diri Terhadap Sikap Mahasiswa Pria Katolik Dalam Mengkonsumsi Alkohol Di Kota Jayapura - Sinaga, Dominika Rotua (Jurnal Masalah Pastoral, 2020)
The aim of this study was to investigate the correlation between Self-concept with the attitude of Male Catholic students for alcohol use in Jayapura City. Participants were 50 male Catholic College students who are from five districts in Jayapura City. The male Catholic College students from 18-27 years old. The approach of this study was quantitative descriptive. Data were collected by a valid and reliable questionnaire, observation and Interview. The study finds a significantly positive correlation between Self-Concept and the attitude of Male Catholic college students in Jayapura City.